2013
DOI: 10.1128/jvi.03403-12
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Phagocytic Activity of HIV-Specific Antibodies Correlates with Natural Production of Immunoglobulins with Skewed Affinity for FcγR2a and FcγR2b

Abstract: While development of an HIV vaccine that can induce neutralizing antibodies remains a priority, decades of research have proven that this is a daunting task. However, accumulating evidence suggests that antibodies with the capacity to harness innate immunity may provide some protection. While significant research has focused on the cytolytic properties of antibodies in acquisition and control, less is known about the role of additional effector functions. In this study, we investigated antibody-dependent phago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 59 publications
(69 reference statements)
3
97
0
Order By: Relevance
“…Since then, patient studies support the notion that IgG glycosylation directly impacts function. For autoimmunity, terminal galactosylation (27) and terminal sialylation (2-4, 6) are now established factors in immune modulation, whereas fucosylation has been shown to correlate with antibody-dependent cell-mediated viral inhibition (ADCVI) activity in the context of HIV infection (28,29) as well as antibody-dependent cellular cytotoxicity (ADCC) in vitro (30). For ADCC, structural rearrangements associated with the presence of fucose within the Fc domain appear to account for the functional shift (31), but it remains unclear how fucosylation translates into differential ADCVI activity.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, patient studies support the notion that IgG glycosylation directly impacts function. For autoimmunity, terminal galactosylation (27) and terminal sialylation (2-4, 6) are now established factors in immune modulation, whereas fucosylation has been shown to correlate with antibody-dependent cell-mediated viral inhibition (ADCVI) activity in the context of HIV infection (28,29) as well as antibody-dependent cellular cytotoxicity (ADCC) in vitro (30). For ADCC, structural rearrangements associated with the presence of fucose within the Fc domain appear to account for the functional shift (31), but it remains unclear how fucosylation translates into differential ADCVI activity.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the rare HIV-1 infected subjects who naturally completely control viral replication (termed "elite controllers") also illustrate the integral role that ADCC and ADCP play in natural immunity. The trend observed in several studies of natural infection was for higher levels of ADCC antibodies and a response skewed to IgG3/1 subclasses in HIV-1 controllers compared to an IgG4/2 subclass skewing in viremic individuals [18,61,71,72]. ADCC-antibodies are produced more rapidly following infection than neutralizing antibodies, which typically take months or years to develop [46,49].…”
Section: In Vivo Studies Iii: Natural Infectionmentioning
confidence: 98%
“…Forthal et al (2001) found plasma from acutely infected patients and normal NK effector cells were able to inhibit viral replication, suggesting a role for antibody and NK cells in early control of infection [68]. The assay can use NK cells or monocytes for killing of infected targets [18]. Other formats measured Fc-dependent direct inhibition of replication in primary macrophages [20].…”
Section: Cell Based Functional Assays For Fcr Activating Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations